La notation musicale : son origine, son évolution - Thibaut, Jean Baptiste (Saint Petersburg Kügelgen, Glitsch & Co., 1912)
Conference at the Imperial Conservatory in St Petersburg, under the patronage of H.S.H. Princess Hélène of Saxony-Altenburg, 11/24 February 1912
Ex libris Hector Colard (plate)
Keywords: 20th Century (1901-2000); Notation; Music history